OPTIMIZING MEDICAL TERMINOLOGY INTERPRETATION AND ICD-10 CODING SKILLS FOR SURGICAL CASES AT RSKB ROPANASURI PADANG - Khumaira, Nurul Fitri; Yastori, Yastori; Kader, Shaola Syafrullah; Novita, Dian (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service activity focused on improving the understanding of medical terminology and ICD-10 coding accuracy for surgical cases at RSKB Ropanasuri Padang. The main problem identified was the difficulty medical record officers faced in correctly interpreting medical terminology used by doctors, especially in surgical diagnoses. This often led to inaccurate coding, impacting the hospital's data and finances. The solution provided was a comprehensive training session, which included socialization, case studies, and discussions to enhance participants' understanding of medical terminology and improve their ICD-10 coding skills. The results showed significant improvement in participants' ability to interpret diagnoses and apply the correct ICD-10 codes, with pretest scores increasing by 71.43% after the training. This study emphasizes the importance of standardized medical terminology and continuous training for improving diagnostic coding accuracy in healthcare settings. Further training on diverse medical cases is recommended to enhance coding proficiency.